Analysis of corporate volunteering in internal market orientation and its effect on job satisfaction - Robledo,José Luis Ruizalba (2015)
This study analyses some of the factors comprising Internal Market Orientation (IMO) in family businesses in Andalusia (Spain): Management Concern, Training and Work-Family-Balance. Corporate Volunteering (CV) has been incorporated for the first time in IMO. A statistical analysis shows that CV can be inserted within the dimension of response to internal market intelligence and, its incorporation is proposed for future IMO models as a part of Corporate Social Responsibility (CSR). The impact of some factors on Job Satisfaction has also been considered. The two most influential factors on Job Satisfaction are CV and Work-Family-Balance.